Surface water-quality modeling - Chapra, Steven C. (McGraw-Hill series in water resources and environmental engineering, 1997)
Surface Water-Quality Modeling presents the wealth of knowledge that Dr. Chapra has acquired through his extensive study and scholarship on surface water quality. The book provides both a thorough introduction to modeling fundamentals along with in-depth descriptions of how a variety of pollutants move and react with a variety of water bodies. Effectively written in a "user-friendly" format, the text facilitates independent learning while balancing traditional analytical models with more recent computer-oriented approaches.